2011
DOI: 10.1111/j.1742-7843.2011.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti‐Inflammatory Activities of Sulphated Polysaccharides from the Red Seaweed Gracilaria cornea

Abstract: Seaweeds have attracted special interest as good sources of sulphated polysaccharides (SP) for use in pharmaceutical industries and biotechnology. In this study, we evaluated the effects of SP from the red seaweed Gracilaria cornea (Gc-TSP) in nociceptive and inflammatory models. In mice, Gc-TSP (3, 9 or 27 mg ⁄ kg) significantly reduced nociceptive responses, as measured by the number of writhes, at all tested doses. In a formalin test, Gc-TSP significantly reduced licking time in both phases of the test at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 39 publications
2
66
0
1
Order By: Relevance
“…Seaweed polysaccharides have various biological activities, including anti-inflammation (Coura et al, 2012;Jung, Jin, Ahn, Lee, & Choi, 2013;Simpi, Nagathan, Karajgi, & Kalyane, 2013). NO is an inflammatory mediator induced by inflammatory cytokines or bacterial LPS in various cell types including macrophages (Swindle & Metcalfe, 2007).…”
Section: Effect Of the Seaweed Polysaccharides On No Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seaweed polysaccharides have various biological activities, including anti-inflammation (Coura et al, 2012;Jung, Jin, Ahn, Lee, & Choi, 2013;Simpi, Nagathan, Karajgi, & Kalyane, 2013). NO is an inflammatory mediator induced by inflammatory cytokines or bacterial LPS in various cell types including macrophages (Swindle & Metcalfe, 2007).…”
Section: Effect Of the Seaweed Polysaccharides On No Secretionmentioning
confidence: 99%
“…The sulfated polysaccharides from the brown seaweeds Sargassum wightii and Halophila ovalis (Yuvaraj et al, 2013) and the red seaweeds Gracilaria cornea (Coura et al, 2012) and Caulerpa racemosa (Ribeiro et al, 2014) have anti-inflammatory activities in vivo. In a BV2 microglia cell model, Park et al (2011) demonstrated that the anti-inflammatory activity of fucoidan (a sulfated polysaccharide) from the brown seaweed Fucus vesiculosus occurred by suppressing activation of nuclear factor-kB (NF-kB) and downregulating the mitogen-activated protein kinase (MAPK) and Akt pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Red seaweed Gracilaria cornea GC-TSP (27 mg/kg) showed significant antinociceptive effects (at 60 min) compared to the other doses tested (3 and 9 mg/kg). 37 In contrast, SP sf from red seaweed S. filiformis (1 mg/kg) and Cc-SP2 of green seaweed Caulerpa cupressoides (9 mg/kg) showed more significant antinociceptive effects than higher concentrations tested. Therefore, this result indicate that the antinociceptive action of Sw-SP and Ho-SP could also occur via a central acting mechanism, similar to red seaweeds G. cornea and B. seaforthii.…”
Section: Discussionmentioning
confidence: 60%
“…18,35,36 Currently, sulfated polysaccharides of different seaweed species provide new analgesic and anti-inflammatory agents. 8,37 To the best of our knowledge, no reports have been documented for the anti-inflammatory activity of sulfated polysaccharides extracted from seagrass species. This study demonstrated that sulfated polysaccharides obtained from the brown algae S. wightii and seagrass H. ovalis, produce antinociceptive and anti-inflammatory effects in models of nociception (formalin test and hot plate test), acute inflammation (carrageenan-induced paw edema test, peritonitis model), and chronic inflammation (FCAinduced arthritis test).…”
Section: Discussionmentioning
confidence: 95%
“…Several extracts, fractions, and natural products isolated from seaweeds have demonstrated effective anti-HIV activity (Vo and Kim, 2010), making it an interesting base from which to develop new medicines. Of the seaweeds, red seaweeds produce natural products such as acetogenins (Gutiérrez-Cepeda et al, 2011), sesquiterpenes (Chen et al, 2016), monoterpenes (Silva et al, 2015), bromophenols (Popplewell and Northcote, 2009), and sulfated polysaccharides (Coura, 2012) that can be used for anti-HIV drug development.…”
Section: Introductionmentioning
confidence: 99%